USAHA MENURUNKAN PENGGUNAAN PESTISIDA KIMIA DENGAN PROGRAM PENGENDALIAN HAMA TERPADU (Efforts to Reduce Chemical Pesticides Use through Integrated Pest Management Program) - Joko Mariyono; Irham Irham (Jurnal Manusia dan Lingkungan, 2001)
ABSTRAKPestisida kimia merupakan bahan beracun yang menyebabkan pencemaran lingkungan dan berbahaya bagi kesehatan manusia. Penggunaannya yang berlebihan telah menimbulkan biaya eksternal yang sangat tinggi. Sejak tahun 1989 Pemerintah Indonesia telah berusaha mengurangi penggunaan pestisida kimia melalui program Pengendalian Hama Terpadu (PHT) Untuk mengetahui dampak program PHT, digunakan fungsi permintaan pestisida kimia. Analisis ini menggunakan data sekunder selama sembilan tahun yang diambil dari empat kabupaten wilayah Yogyakarta. Hasil analisis menunjukkan bahwa  dampak program PHT telah berhasil mengurangi penggunaan pestisida kimia pada padi dan kedelai. Penurunan penggunaan pestisida kimia disebabkan oleh kenaikan harga dan penyebaran teknologi PHT. Turunnya penggunaan pestisida kimia ini akan meningkatkan kualitas lingkungan dan kesehatan manusia karena tersedia bahan pangan yang residu pestisida kimianya rendah. ABSTRACTChemical pesticide is a poisonous agent that causes deterioration on environment quality and thereatens to human health. It causes considerable high externat cost. Sice 1989 the Government of Indonesia had removed chemical pesticide subsidy and introduced a new program called Integrated {est <amage,emt (IPM)  in ornder to reduce chemical pestidice use. The objectives of this research was to determine the impact of IPM Program on cemical pesticide use in rice and soybean cultivation. To determine the impact, ademand model of cemical pesticide was employed. Time series secondary data for nine years collected from related institutions in four revencies of Yogyakarta were utilized as the basic analysis. Results of the analysis indicated that chemical pesticide uses in rice and soybean cultivation have declined. The reduction of chemical pesticide use was caused by the increase of chemical pesticide price due to the discontinuation of chemical pesticide subsidy, and dissemination of IPM program. It implied that the program will improve environment quality and human health, and provide  food with low chemical pesticide residue.